2015
DOI: 10.1007/s12038-015-9530-8
|View full text |Cite
|
Sign up to set email alerts
|

The substance P/NK-1 receptor system: NK-1 receptor antagonists as anti-cancer drugs

Abstract: The substance P (SP)/neurokinin (NK)-1 receptor system plays an important role in cancer. SP promotes the proliferation of tumour cells, angiogenesis and the migration of tumour cells. We review the involvement of SP, the NK-1 receptor and NK-1 receptor antagonists in cancer. Tumour cells overexpress NK-1 receptors, which are involved in their viability. This overexpression suggests the possibility of specific treatment against tumour cells using NK-1 receptor antagonists, thus promoting a considerable decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 130 publications
2
120
0
Order By: Relevance
“…In this report, our results showed that SP and NK‐1R were expressed at high protein levels in GBC tumor samples. Consistent with previous researches, the activation of NK‐1R dose‐dependently induced the proliferation and invasion of GBC cells, and these effects could be blocked by NK‐1R antagonist. Notably, we also observed that NK‐1R could significantly increase the activity of NF‐κB throuth up‐regulating Akt.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this report, our results showed that SP and NK‐1R were expressed at high protein levels in GBC tumor samples. Consistent with previous researches, the activation of NK‐1R dose‐dependently induced the proliferation and invasion of GBC cells, and these effects could be blocked by NK‐1R antagonist. Notably, we also observed that NK‐1R could significantly increase the activity of NF‐κB throuth up‐regulating Akt.…”
Section: Discussionsupporting
confidence: 90%
“…Over the past decades, the function of peptides and their receptors in tumors have attracted growing interest, and research efforts show that these peptides and receptors can influence cancer progress. One such target could be SP/NK‐1R system, since it is known that NK‐1R can act as a mitogen on several human cancers . Currently, it is still unknown whether NK‐1R exists the same effect in GBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Notably, these effects mediated by SP can be suppressed by NK-1R antagonists. 16 It was reported that SP/NK-1R signaling plays an important role in cancer progression and metastasis, and SP could function as a mitogen in NK-1R expressing tumor cells. 14 For example, SP induced the expression of matrix metalloproteinase 2 (MMP-2) in pancreatic cancer cells, and NK-1R antagonists inhibited MMP-2 expression.…”
mentioning
confidence: 99%